Archaeology and Immersion: Poliphilo’s Staircase to Knowledge .......... 159 - Koch, Nadia J. (Tra l’antica sapientia e l’imaginatio: Nuovi studi sul Polifilo, 2020)
This study intends to locate the Hypnerotomachia Poliphili in the antiquarian studies of the 15th century. For this purpose, it examines the influence of Flavio Biondo’s book on Roman topography, Roma instaurata, and Leon Battista Alberti’s treatise De re aedificatoria; furthermore, the woodcuts of the Hypnerotomachia are confronted with the drawings of ancient monuments by Cyriac of Ancona and other antiquarians. On an art theoretical level, it can be shown how the Hypnerotomachia enhances Alberti’s theory of architecture by describing and systematically integrating the emotions of the viewer in an innovative way, exemplified in Poliphilo’s immersion into the monuments he encounters. A crucial role in this process is played by Filarete’s Trattato di Architettura, which for the first time dealt with the creative capacity of the artist, his fantasia. Both the illustrations of Filarete’s treatise and its narratology seem to have had some influence on the author of the Hypnerotomachia. The then popular dialogical structure offered a pattern for the novel as to how knowledge of art and antiquity could be presented to the reader in a fascinating way. The most important result for the history of classical studies is the method of acquiring knowledge of antiquity, which is revealed in Poliphilo’s encounter with the four obelisks. Here the Hypnerotomachia connects the Aristotelian notions of epistéme and phantasia in order to establish a new field of learning. Since the first edition, the sophisticated design and the mode of storytelling have contributed to spreading a new idea of archaeology among European scholars.